Enhancing the Preparedness of Diploma in Pharmacy Students for the 2025 Exit Exam - Wibowo, Teguh Setiawan; Kusuma Negara, Sri Bintang Sahara Mahaputra (Easta Journal of Innovative Community Services, 2025)
This community service initiative comprises a webinar and a six-month mentorship program designed to equip Diploma in Pharmacy (D3) students with effective strategies for tackling the National Competency Examination (UKOM), a crucial component of the 2025 Exit Exam. Through interactive sessions, participants will gain in-depth insights into question structures, clinical case analysis approaches, and competency-based answering techniques aligned with the latest standards. The program also includes question simulations and comprehensive discussions to enhance participants' overall readiness. This webinar is expected to serve as a strategic platform for students to boost their confidence and competence in facing the UKOM, thereby supporting timely graduation and preparedness for entering the professional workforce.